Temporal lobe involvement: A diagnostic challenge in Japanese encephalitis - Rajashekarmurthy, G R; Keshavamurthy, M L; Panigrahic, Nikitha Kumari; Basavaraja, G V; Srinivas, S K (Indian Journal of Child Health, 2015)
Japanese encephalitis (JE) and herpes encephalitis are the most common endemic and sporadic encephalitis, respectively. A 10-yearold boy, presented with features suggestive of viral meningoencephalitis, had neuroimaging suggestive of herpes encephalitis, but cerebrospinal fluid serology was positive of JE. Temporal lobe involvement in JE may cause problems in differentiating it from herpes encephalitis, which highlights the importance of both neuroimaging and serology for a complete diagnosis.